A state-of-the-art review on LSD1 and its inhibitors in breast cancer: Molecular mechanisms and therapeutic significance - Yang, Guan-Jun; Liu, Yan-Jun; Ding, Li-Jian; Tao, Fan; Zhu, Ming-Hui; Shi, Zhen-Yuan; Wen, Juan-Ming; Niu, Meng-Yao; Li, Xiang; Xu, Zhan-Song; Qin, Wan-Jia; Fei, Chen-Jie; et al. (Frontiers in Pharmacology, 2022)
Breast cancer (BC) is a kind of woman malignant cancer and it has become the most diagnosed cancer worldwide since 2020. Histone methylation is a common biological epigenetic modification mediating varieties of physiological and pathological processes. Lysine-specific demethylase 1 (LSD1), a firstly identified histone demethylase, mediates removal of methyl groups from histones H3K4me1/2 and H3K9me1/2 and plays a crucial role in cancer progression. It is also specifically amplified in breast cancer and contributes to BC tumorigenesis and drug resistance via both demethylase and non- demethylase manners. This review will provide insight into the overview structure of LSD1, summarize its action mechanisms in BC, describe the therapeutic potential of LSD1 inhibitors in BC, and prospect the current opportunities and challenges of targeting LSD1 for BC therapy.